Tuberculous meningitis-related ischemic stroke: A retrospective study from a tertiary care hospital - Xuhui Deng; Qiuhui Huang; Hua Huang; Shengri Chen; Xue Wang; Zhijian Liang (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
Background: Patients with tuberculous meningitis (TBM) are at high risk of ischemic stroke, and stroke is a poor prognosticator of TBM. However, reports regarding the predictors of stroke in TBM patients are scanty. The aim of this study was to investigate the clinical characteristics and predictors of tuberculous meningitis-related ischemic stroke (TBMRIS). Methods: This retrospective study was conducted among TBM patients without traditional vascular risk factors from a tertiary care hospital between January 2017 and November 2022. Patients were divided into TBMRIS group and TBM-only group according to presence of stroke. Clinical, laboratory and radiological variables were compared between the two groups. Predictors of stroke were identified using binary logistic regression analysis. Results: A total of 176 TBM patients were included in the study. Forty-nine patients with stroke were classified as TBMRIS group and 127 patients without stroke were classified as TBM-only group. In TBMRIS group, 41 (83.7 %) patients experienced stroke within 3 months after the onset of meningitis symptoms and 10 (20.4 %) patients presented silent stroke. Stroke occurred in basal ganglia in 57.1 % of patients. About 73.5 % of patients showed multiple stroke lesions and 38.8 % of patients had stroke involving multiple vascular territories. There were significant differences in focal neurological deficit, stage of meningitis, short-term outcome, serum sodium, cerebrospinal fluid (CSF) white cell count, CSF adenosine deaminase (ADA), CSF protein, leptomeningeal enhancement, tuberculoma between TBMRIS group and TBM-only group. Binary logistic regression analysis revealed that focal neurological deficit, CSF white cell count and leptomeningeal enhancement were the independent risk factors for stroke, and tuberculoma was negatively correlated with stroke. Conclusion: Most of TBMRIS develop within 3 months after the onset of meningitis symptoms and basal ganglia is the most frequent site. Multiple stroke lesions and involvement of multiple vascular territories are commonly observed. Focal neurological deficit, CSF white cell count and leptomeningeal enhancement are the predictors of stroke in patients with TBM.